Pathways and magnitude of change and their drivers of public open space in Pokhara Metropolitan City, Nepal - Pokharel, Ramjee Prasad; Khanal, Narendra Raj (Geographical Journal of Nepal, 2020)
Public open space (POS), which is known as production space, is an integral part of an urban area. The pathways of change of POS are directly related to the urbanization process. Several factors play a vital role in creating an open space to satisfy peoples' physical and mental desires. This paper discusses the pathways and magnitude of change of POS and its drivers. This study is based on a detailed study of 32 sampled sites out of a total of 275 sites identified in Pokhara metropolitan city, and interviews with key informants in the concerned sites. The results show that there is no uniform trend in the change of open space. The area has remained constant in some sites whereas it has been decreased in some sites and also increased in some sites. Out of the total, 56.25 percent of patches remained constant in terms of area whereas 40.13 percent patches are decreased and increased in only 3.12 percent patches during the period between 1998 to 2018. There has been a net decrease of 24.652 hectors in the area in total. The increase of 3.12 percent attributed mainly to land pooling from individual ownership whereas the decrease is mainly due to the encroachment by individual people as well as for the construction of public infrastructure especially for expansion of the roads. The changes observed are not only limited to the change in the area but also the layout and the using pattern. Both the natural and the socio-economic factors including government policy are found responsible for such change. On the one hand, natural processes like sedimentation, landslides, floods, vegetation regeneration, cutting edge and on the other hand, government policies for the development of infrastructure facilities, rapid increase in urban area and consequent increase in land value, lack of awareness to the importance of open space among local people including local government are responsible for such change.